COVID-19 and online learning: a scoping review of the challenges faced by students in higher institutions during lockdown - Phiriepa, Antletse; Mapaling, Curwyn; Matlakala, Frans Koketso; Tsabedze, Wandile (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic has undeniably disrupted the education system, prompting many universities and schools to suspend in-person classes in favour of online learning. This transition has been linked to increased levels of academic stress and mental health issues among university students. This study aimed to (i) assess the coverage of articles addressing the challenges faced by students in higher education institutions during lockdown and (ii) identify the coping mechanisms employed by these students. Employing a scoping review methodology, researchers selectively reviewed articles published from 2019 to 2023. Databases such as PubMed, ScienceDirect, Google Scholar, and Sabinet Africa Journals served as sources for data collection, which was subsequently analysed thematically. Findings indicate that psychology students faced multiple challenges during online learning, including elevated stress and anxiety levels, data limitations, and poor network connectivity. To cope with these challenges, students relied on support from family and friends, self-motivation, and effective time management. Consequently, the study highlights the need for pedagogical adaptations, recommending that educators modify their teaching approaches to better engage students in discussions and mitigate the noted challenges.